PENGARUH POSYANDU REMAJA TERHADAP STATUS KESEHATAN REPRODUKSI DI SALAH SATU WILAYAH PUSKESMAS DI KABUPATEN BANDUNG TAHUN 2021 - Iceu Mulyati (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2021)
Adolescence is a period of transition or movement from childhood to adulthood, adolescents will experience challenges both from themselves and from outside. This creates confusion for adolescents who are worried that adolescents will engage in irresponsible sexual behavior. is one of the activities that can overcome adolescent problems. The research method uses Quasi Experimental adolescents who are provided with youth posyandu services, measurement of reproductive health status before and after. A sample of adolescents aged 10-18 years. Analysis using the Wilcoxcon test obtained reproductive health status, namely knowledge before 69.2% less while after 71.8% the level of knowledge was good, p-Value 0.000, anemia status before 25.6% anemia and after becoming 5.1% who experienced anemia p-Value 0.01, nutritional status before 69.2 underweight nutritional status, and after 59% normal nutritional status P-value 0.004 from the results of this study it can be concluded that there is an influence of adolescent posyandu on improving reproductive health Therefore, the youth posyandu should continue to be implemented.